Adaptation of Grid Tied Photovoltaic (GT-PV) System as Retrofit Renewable Energy Model for Single-Family House in UAE - Chohan, Afaq Hyder; Memon, Zulfiqar Ali; Che-Ani, Adi Irfan; Arar, Mohammad Shihadeh; Awad, Jihad (International Journal of Integrated Engineering, 2021)
Gulf Cooperation Countries (GCC) governments are encouraging advances in renewable energy and its deployment to reform domestic energy market policy. GCC countries including United Arab Emirates (UAE) all have begun to explore renewable energy technologies. This research intended to develop a framework model to use Grid Tied photovoltaic renewable energy (GT-PV) in the housing design of the GCC region particularly in UAE. In this regard, research has analyzed the various types of housing plans and worked out the possibilities of retrofit design to adapt renewable energy model to implement (GT-PV) in existing housing for their energy needs. This study has determined the total energy need of each type of house, data of energy need was statically analyzed, and renewable energy output was calculated. The end result of research has surfaced a comprehensive model to design a grid-tied photovoltaic renewable energy system to cater the need for private housing in UAE.